Συμβολὴ στὴν μελέτη τῆς νομισματοκοπίας τῆς Πλωτινοπόλεως: ἕνας νέος εἰκονογραφικὸς τύπος - Τασακλάκη, Μαρίνα; Κουτσουμανῆς, Ματθαῖος (Tekmeria, 2013)
<!--[if gte mso 9]> Normal 0 false false false <![endif]--><span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; letter-spacing: -.1pt; mso-ansi-language: EN-US; mso-fareast-language: EL; mso-bidi-language: AR-SA;" lang="EN-US">A bronze coin of Plotinopolis has been recently acquired by the Archaeological Museum of Komotini. The octassarion of Caracalla discussed in this paper <span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; letter-spacing: -.1pt; mso-ansi-language: EN-GB; mso-fareast-language: EL; mso-bidi-language: AR-SA;" lang="EN-GB">and dated between 212 and 215 BC,<span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; letter-spacing: -.1pt; mso-ansi-language: EN-US; mso-fareast-language: EL; mso-bidi-language: AR-SA;" lang="EN-US"> represents on the reverse <span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; letter-spacing: -.1pt; mso-ansi-language: EN-GB; mso-fareast-language: EL; mso-bidi-language: AR-SA;" lang="EN-GB">Hades abducting Persephone, a new iconographic type not only of the city but also of the entire Province of Roman Thrace. Parallels of this rare iconography occur mainly in Asia Minor<span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; letter-spacing: -.1pt; mso-ansi-language: EN-US; mso-fareast-language: EL; mso-bidi-language: AR-SA;" lang="EN-US">, in cities where the textual and archaeological evidence of the cult of Pluton indicate the presence of a sanctuary dedicated to the god in the surrounding area. Furthermore, since numismatic types related to Pluton were often issued during the Severans, this particular coin issue could be connected to the imperial propaganda and to the arrival of Caracalla in Thrace.<!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->